Catalyzing new business models: The transformative influence of the partnership platform for the Amazon (PPA) on sustainable development in the Brazilian Amazon - Senger, Sacha; Francesconi, Wendy; Caldas De Oliveira, Bernardo (2024)
Founded in 2017, the Partnership Platform for the Amazon (PPA) champions sustainable development and biodiversity conservation in the Brazilian Amazon. A 2022–2023 study showcased a substantial increase in active PPA network participants, peaking at 137 organizations, with 31% of total relationships attributed to the PPA’s influence. This represents heightened influence and engagement, and significant strides in relationship building. It underscores the PPA's crucial role in fostering partnerships, particularly in investment, technical cooperation, and institutional collaboration for advancing sustainable development in Amazonia. [1]